Proceedings of the Ocean Drilling Program, 150 Scientific Results 1996
DOI: 10.2973/odp.proc.sr.150.040.1996
|View full text |Cite
|
Sign up to set email alerts
|

Organofacies Variations in Sediments from the Continental Slope and Rise of the New Jersey Continental Margin (Sites 903 and 905)

Abstract: This study describes molecular organic geochemical investigations of 14 samples from Site 903 off New Jersey, as well as bulk analysis of a great number of sediments from Sites 903 and 905. Detailed lipid analysis of the solvent-extractable organic matter exhibits a complex assemblage of marine, terrigenous, and bacterial compounds. rc-Alkanes and n-alcohols are the most abundant compounds in extracts of sediments from Site 903, followed by steroidal alcohols in considerably smaller concentrations that decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Similar values are recorded in late Pleistocene-age pelagic sediments (Prahl et al, 1989;Sikes et al, 1991); Holocene-age continental margin sediments from upwelling areas contain one to three orders of magnitude higher concentrations of C 37 alkenones (McCaffrey et al, 1990;Kennedy and Brassell, 1992). Organic geochemical analyses from Ocean Drilling Program (ODP) Site 958 thus help to confirm the diagenetic longevity of alkenones inferred from storage experiments (Sikes et al, 1991) and from other reports of their occurrence in pre-Pleistocene sediments (Marlowe, 1984;Brassell, 1993;van der Smissen and Rulkotter, 1996). The U k′ 37 time series is displayed in Figure 3.…”
Section: Resultssupporting
confidence: 66%
“…Similar values are recorded in late Pleistocene-age pelagic sediments (Prahl et al, 1989;Sikes et al, 1991); Holocene-age continental margin sediments from upwelling areas contain one to three orders of magnitude higher concentrations of C 37 alkenones (McCaffrey et al, 1990;Kennedy and Brassell, 1992). Organic geochemical analyses from Ocean Drilling Program (ODP) Site 958 thus help to confirm the diagenetic longevity of alkenones inferred from storage experiments (Sikes et al, 1991) and from other reports of their occurrence in pre-Pleistocene sediments (Marlowe, 1984;Brassell, 1993;van der Smissen and Rulkotter, 1996). The U k′ 37 time series is displayed in Figure 3.…”
Section: Resultssupporting
confidence: 66%
“…Subsequent Δ 14 and Δ 21 desaturation (positions relative to the carbonyl group), perhaps concerted, generates alka-15,22-dien-2-ones and alka-16,23-dien-3-ones, which serve as precursors for alkatrienones (e.g., alka-8,15,22-trien-2-ones) and alkatetraenones (e.g., alka-8,15,22,29-tetraen-2-ones) following successive Δ 7 and Δ 28 desaturation, respectively. The latter series of desaturation reactions seems likely to occur as separate, discrete steps, based on specific lines of evidence, including the differences in δD values for the C 37 alkadien-2-one and alkatrien-2-one attributed to the desaturation step [van der Meer et al, 2013], and the independent controls on the relative abundance of the C 37:4 alkenone [Rosell-Melé, 1998;Sikes and Sicre, 2002;Bendle et al, 2005], augmented by the single reported occurrence of a C 37:5 alkenone in Antarctic lake sediments [Jaraula et al, 2010]. In addition, the discovery of alkatrienones formed by Δ 14,21,28 desaturation in lake sediments from Alaska and Greenland [Longo et al, 2013] reveals that Δ 28 desaturation can occur prior to Δ 7 desaturation, confirming that these processes are distinct.…”
Section: Pathways Of Alkenone Biosynthesismentioning
confidence: 99%
“…High methane concentrations suggest that the deposited labile marine organic matter was not completely oxidized in the sulfate reduction zone (where the available carbonate anions appear to have been consumed for dolomite precipitation), but its decomposition was largely completed in the (supposedly upper) methanogenic zone (cf. van der Smissen and Rullkötter 1996). Thus, the high preserved TOC level in this interval may be a result of the high proportion of terrigenous organic matter, which has not yet been metabolically degraded.…”
Section: Oligocene To Lower Middle Miocene Dolomitesmentioning
confidence: 94%
“…The interpretation of systems tracts more than 550 m below sea floor (mbsf) is from Vecsei and Hoppie (1996), and those above 550 mbsf are from McCracken et al (1996). Data on the organic matter, measured outside the diagenetic carbonates, are from van der Smissen and Rullkötter (1996). The ratio of marine to terrigenous organic matter is indicated, for example, by the composition in diverse alipathic hydrocarbons, nalcohols (e.g., long-chained alcohols and steroidal alcohols), the concentration of sterols, and the distribution of short-and long-chain even-carbon-number homologs of n-fatty acids (van der Smissen and Rullkötter 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation